An Epidemiological and Economic Simulation Model to Evaluate Strategies for the Control of Bovine Virus Diarrhea in Germany - Gethmann, Jörn; Probst, Carolina; Bassett, Jason; Blunk, Pascal; Hövel, Philipp; Conraths, Franz J. (Frontiers in Veterinary Science, 2019)
Models can be used to plan, evaluate and improve programs for animal disease control. In Germany, a nationwide compulsory program to eradicate Bovine viral diarrhea (BVD) is in force since January 2011. As it is associated with substantial expenditures, the program is currently under revision. To provide the basis for a science-based decision on the future course of BVD control in Germany, we evaluated 13 scenarios (sc1-13) with respect to the chance of reaching freedom from disease and their economic implications for a period of 20 years (2011-2030). To simulate the impact of different control strategies on disease dynamics, a disease spread model was developed. To estimate the effects of a transient infection (TI) on animal level, a gross margin analysis was performed. To assess the value of cattle that died prematurely, a valuation model was used. Finally, an economic model was developed to perform a cost-benefit analysis and to compare each control scenario with a baseline setting with no BVD control. Costs comprised the expenditures for diagnostics, vaccination, preventive culling and trade restrictions. Benefits were animal and production losses avoided by having control measures in place. The results show that reducing the PI prevalence on animal level to 0 % is only feasible in scenarios that combine antigen or antibody testing with compulsory vaccination. All other scenarios, i.e. those based exclusively on a “test and cull” approach, including the current control program, will, according to the model, not achieve freedom of BVD by 2030. On the other hand, none of the scenarios that may lead to complete BVD eradication is economically attractive (benefit-cost ratio [BCR] between 0.64 and 0.94). The average direct costs of BVD in Germany are estimated at 113 million Euros per year (34 to 402 million Euros), corresponding to 28.3 million Euros per million animals. Only the concepts of the former and the current national BVD control program (“ear tag testing and culling”) may reduce the BVD prevalence to 0.01 % with an acceptable BCR (net present value of 222 and 238 million Euros respectively, with a BCR of 1.22 and 1.24).